Analisis Pengaruh Brand Ambasador terhadap Keputusan Pembelian di Lazada - Widiawati, Diah; Wicaksono Sudjarwo, Aleksius Bondan; Suprayitno, Adi (University of Merdeka Malang, 2022)
This study aims to examine the influence of brand ambassadors on purchasing decisions at Lazada. This type of research is explanatory research through a quantitative approach. Data collection was obtained through the distribution of online questionnaires to Economics and Business students at University of Merdeka Malang who had purchased and seen Lee Min Hoo's version of Lazada advertisement. The questionnaires collected were 70 questionnaires. The analytical method used is descriptive analysis and multiple linear regression analysis to test the hypothesis using SPSS 25 software. in purchasing decisions at lazada. The credibility variable has the biggest influence on product purchasing decisions at Lazada